Mind mapping: an effective model to improve thematic learning outcomes - Istikomah, Desi; Koeswanti, Henny Dewi (Jurnal Pendidikan dan Pengajaran, 2019)
This study aimed at improving students' learning outcomes of class V in Theme 6 using a mind mapping model. This research was conducted in 2 cycles, i.e. cycle 1 and cycle 2, with each cycle consisting of 3 sessions. The research subjects were 16 students of class V SDN Kutowinangun 10 Salatiga. The research design was arranged based on planning, action, observation, and reflection. Result shows that there is an increase in learning completeness, from 31.25% in pre-cycle to 56.25% and 81.25% in cycle I and cycle II, respectively. Therefore, mind mapping model may increase students' learning outcomes.